What I want is what I get : an investigation of the desirability bias. - Kuah, Aik Sze. (2008)
This study investigates the desirability bias, which occurs when people over-estimate the likelihood of desirable outcomes and under-estimate the likelihood of undesirable outcomes, even though the objective probabilities are known (Budescu and Bruderman, 1995). This study attempts to examine the presence of the desirability bias in the judgement-making process of local undergraduates.